The history of settlement in Late Bronze Age and Early Iron Age Crete: a review and synthesis - Pollard, Dominic (Journal of Greek Archaeology, 2023)
The period between 1450 and 550 BCE witnessed profound changes in the economic, political and cultural structures of the island of Crete (Figure 1). Around 1450, a period of turbulence greatly disrupted the Bronze Age palatial system. Once a network of largely independent regional centres (perhaps increasingly dominated in central Crete by the site of Knossos), the destruction of almost every palace around this time was followed by the consolidation of a single state governed by the enduring palace of Knossos. This Final Palatial system ultimately collapsed in the late 14th or early 13th century BCE. Around the turn of the 12th century, settlement on the island reoriented towards more elevated, inland and defensible locations, though a few lower-lying sites and former centres of occupation endured. Between the 10th and 8th centuries, communities gradually nucleated into larger, strategically located settlements, many of which went on to become regional centres of the 8th-7th centuries, or historically attested poleis. By the 6th century, the island was a patchwork of these small, independent city-states, in a pattern quite distinct from the Final Palatial system which had occupied the same landscape some eight centuries previously.